Climatology of Nighttime Upper Thermospheric Winds From Fabry‐Perot Interferometer 2011–2019 Measurements Over Kelan (38.7°N, 111.6°E), China: Local Time, Seasonal, Solar Cycle, and Geomagnetic Activity Dependence. Issue 9 (24th September 2020) - Yang, Changjun; Zhao, Biqiang; Jin, Yuyan; Huang, Cong; Yao, Xin; Wan, Weixing
Abstract: For the first time, we develop a local time and day of year dependent climatological model in different geomagnetic activity based on 630.0 nm Fabry‐Perot Interferometer (FPI) measurements over Kelan (38.7°N, 111.6°E) during 2011–2019. With this model, we analyze the regional climatological characteristics of nighttime thermospheric neutral winds, and a comparison is made with two recent versions of the Horizontal Wind Model series (HWMs), HWM07 and HWM14. Due to the location of Kelan far from the northern magnetic pole longitude at middle latitude, the statistical characterizations of meridional and zonal winds show some unique local time, seasonal, solar cycle and geomagnetic activity dependence. There are predominantly annual variations of horizontal winds characterized by rapid transitions from eastward December winds to westward or less eastward June winds and largest equatorward meridional winds during summer months. To some degree, the wind patterns show casual solar activity dependence especially for the zonal component. The maximum southward winds show negative relationship with increasing solar activity in summer months, while the maximum eastward winds present negative trend in winter months. The Kp dependencies are characterized by larger westward perturbation winds for all night and enhanced northward winds in the premidnight sector and equatorward surges in the postmidnight sector during strongly active conditions. With increasing solar flux, the westward perturbation winds become weaker at nights. Results also reveal that HWM14 predictions are in better agreement with Kelan FPI winds in the shape and magnitude than HWM07, and the consistency improves with increasing Kp. Key Points: We construct climatological models of thermospheric winds with Kelan FPI during 2011–2019 under quiet and disturbed geomagnetical conditions We evaluate the applicability of HWM07 and HWM14 over Kelan and find better agreement for HWM14 predictions especially during geomagnetically active periods We make a comprehensive analysis of the statistical characteristics of seasonal, local time, solar activity, and geomagnetic activity dependence of thermospheric winds over Kelan